1995
DOI: 10.1288/00005537-199506000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative ketorolac tromethamine and postoperative hemorrhage in cases of tonsillectomy and adenoidectomy

Abstract: The charts of 258 patients undergoing tonsillectomy with or without adenoidectomy between June 1991 and June 1993 were reviewed. One hundred sixty-nine of these patients received ketorolac tromethamine during the perioperative period as a nonnarcotic alternative for postoperative pain management. The incidence of postoperative hemorrhage among patients who received ketorolac tromethamine was 10.1%, compared to 2.2% in those patients who received narcotic analgesia only. The average time to adequate oral intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Surgeries varying from complex nephrectomy 14 to laproscopic cholecsytectomy 7 and anterior cruciate ligament reconstruction 1 have all had beneficial postoperative analgesia using Toradol. However, there is little concensus on its safety after spinal surgery because of concerns of the risks of epidural bleeding and negative affects on spinal fusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Surgeries varying from complex nephrectomy 14 to laproscopic cholecsytectomy 7 and anterior cruciate ligament reconstruction 1 have all had beneficial postoperative analgesia using Toradol. However, there is little concensus on its safety after spinal surgery because of concerns of the risks of epidural bleeding and negative affects on spinal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Reports of fatal bleeding have occurred in both adult and pediatric populations specifically in otolaryngology cases involving tonsillectomies and sinus surgery. 3,11 In addition, specifically related to orthopedics, decreased spinal fusion is noted in patients who have used Toradol after multilevel lumbar surgery. 9 These adverse reactions have contributed to a reluctance to use Toradol in spine surgeries and it is currently primarily used in general orthopedics for supplementary analgesia for knee and hip replacements 6 or as a main line drug for use in ambulatory orthopedic cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 There have been conflicting studies in the otolaryngology literature with regard to an increased risk of post-operative hemorrhage following tonsillectomy with the use of parenteral ketorolac. 1,9 Agrawal et al identified no significant increased bleeding risk with ketorolac use, while Gallagher et al found a 5-time increased bleeding risk. 1,9 For gastrointestinal bleeding, Strom et al found a small association between ketorolac and gastrointestinal bleeding (odds ratio, 1.3), especially when the medication was administered for more than 5 days, dosing greater than 105 mg daily, or in patients aged 65 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the present study in which the patients who received both diclofenac and paracetamol intraoperatively (group B) used signi® cantly fewer rescue analgesics during their stay at the postoperative ward. However, one widely disputed sideeffect of NSAIDs has been an increased risk of bleeding (13,14). In contrast, several other studies of diclofenac have reported the absence of any such risk (7± 10, 15).…”
Section: Intra -And Postoperati ×E Bleedingmentioning
confidence: 99%